2021
DOI: 10.1175/jamc-d-20-0155.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Global Warming on Snow in Ski Areas: A Case Study Using a Regional Climate Simulation over the Interior Western United States

Abstract: A high-resolution (4 km) regional climate simulation conducted with the Weather Research and Forecast (WRF) model is used to investigate potential impacts of global warming on skiing conditions in the interior western United States (IWUS). Recent past and near-future climate conditions are compared. The past climate period is from November 1981 to October 2011. The future climate applies to a 30-year period centered on 2050. A pseudo global warming approach is used, with the driver re-analysis dataset perturbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In Yellowstone National Park, for example, found that the length of the snow season at the end of century (2061-2090) could decline by 16 and 27% over present under RCP4.5 and RCP8.5, respectively, with similar or greater declines in the number of days suitable for over-snow vehicles. Lackner et al (2021) projected that under RCP8.5 over the 30-year period centered on 2050, the number of ski days during the core of the season will be reduced from 6 to 29 days at ski areas within the GYA.…”
Section: The Seasonal Cycle Of Precipitationmentioning
confidence: 99%
“…In Yellowstone National Park, for example, found that the length of the snow season at the end of century (2061-2090) could decline by 16 and 27% over present under RCP4.5 and RCP8.5, respectively, with similar or greater declines in the number of days suitable for over-snow vehicles. Lackner et al (2021) projected that under RCP8.5 over the 30-year period centered on 2050, the number of ski days during the core of the season will be reduced from 6 to 29 days at ski areas within the GYA.…”
Section: The Seasonal Cycle Of Precipitationmentioning
confidence: 99%
“…We only included papers that contained analyses with human-dimensions data to avoid making speculations on how climate change may affect people without having data related to those people. For instance, a paper investigating the change in snowpack under climate change may have implications for outdoor recreation and skiing, but if the paper did not explicitly address that using human-dimensions data (e.g., visitation data, spending data, interviews, surveys), we would not include it [e.g., [17][18][19]. Similarly, we did not include papers without original data collection, such as proposed frameworks or conceptual models [e.g., 20,21].…”
Section: Methodsmentioning
confidence: 99%
“…For analysis of historical water use, snowpack, and hydrological changes in Utah, see Khatri and Strong (2020). Additionally, more research on projected changes to snowfall and snowpack at Utah resorts is needed to better understand future water and snowmaking needs (eg Lackner et al 2021). Future studies could also examine how the characteristics of a resort (eg size, location, visitor profile) relate to the ability of a resort to adapt and their perceptions of barriers to adaptation.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…MountainResearchdays at lower-elevation resorts in the western United States, and that natural ski days (ie without snowmaking) may decline by around 30 days per season across Utah resorts by 2050 under RCP 8.5(Lackner et al 2021). Utah ski resort managers reported needing to be open for 97-120 days a season, with most stating they required over 100 days, which is a common threshold used in the literature(Koenig and Abegg 1997).…”
mentioning
confidence: 99%